Addressing the rising fear of nomophobia among medical students - Gabrielle Vivian Rhonda Desouza; Esha Saqlain; Ahsan Shabbir; Hassan Ahmed (Journal of the Pakistan Medical Association)
Dear Editor, I am writing to draw your attention to an escalating fear of nomophobia in the medical student community. Nomophobia or no mobile phobia is a self-build fear of missing out on mobile phones, which is becoming prevalent in the younger generation. It’s a psychological condition where people show signs of anxiety and stress upon losing their smartphones 1. Nomophobia's impact on medical students is far more alarming due to the demanding nature of their educational pattern and the simultaneous role of technology in their educational and professional development.